Study of the action of tamoxifen on the mammary gland epithelium of premenopausal patients by lysosome quantification - Tanaka, Carlos ltio; Gebrim, Luiz Henrique; Lima, Geraldo Rodrigues de; Simões, Manuel de Jesus (São Paulo Medical Journal, 1997)
Tamoxifen is an antiestrogen drug widely utilized for the adjuvant hormonal treatment of breast carcinoma. Its use in the primary prophylaxis of this disease is currently being proposed. Although the drug has few side effects, its precise action on breast tissue that has not undergone neoplastic transformation has not been fully elucidated. This prospective, randomized study assessed the estrogen activity of tamoxifen on the mammary gland epithelium of premenopausal patients using a quantitative analysis of mammary epithelium lysosomes identified by the cytochemical technique of GOMORI for acid phosphatase and by light microscopy. Tamoxifen significantly increased the number of lysosomes only during the secretory phase of the menstrual cycle. We concluded that the early effect of the drug on normal mammary tissue is synergistic with the effect of estrogen during the premenopausal period.